2008
DOI: 10.1108/jpbafm-20-04-2008-b002
|View full text |Cite
|
Sign up to set email alerts
|

The association between government expenditure and economic growth: granger causality test of us data, 1947-2002

Abstract: Wagner’s Law and Keynesian’s theory are two widely accepted yet contrasting propositions. This paper employs Granger causality test on US federal government data, from 1947 to 2002. We used aggregate data as well as disaggregate data with the sub-categories of five federal expenditures, including: national defense, human resources expenditure, physical resources expenditure, net interest payment, and other expenditure. The results of our study suggest that total federal government expenditure is more consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 7 publications
2
28
1
2
Order By: Relevance
“…However, there exists a negative short run relationship between one lag levels of government capital expenditure and manufacturing output. The empirical result of positive relationship between manufacturing output and government capital expenditure is in agreement with the findings of Chih-Hung Liu, et al (2008), Mwafaq (2011), Muritala and Taiwo (2011), Sikiru and Umaru (2011) and Njoku, Okezie, and Ngozi (2014), which confirms that large public expenditure has positive and significant impact on economic growth which may be brought about through its influence on manufacturing output in the Nigerian economy. Interestingly, the result reveals that recurrent expenditure at level and its lagged value have negative effect on manufacturing output.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…However, there exists a negative short run relationship between one lag levels of government capital expenditure and manufacturing output. The empirical result of positive relationship between manufacturing output and government capital expenditure is in agreement with the findings of Chih-Hung Liu, et al (2008), Mwafaq (2011), Muritala and Taiwo (2011), Sikiru and Umaru (2011) and Njoku, Okezie, and Ngozi (2014), which confirms that large public expenditure has positive and significant impact on economic growth which may be brought about through its influence on manufacturing output in the Nigerian economy. Interestingly, the result reveals that recurrent expenditure at level and its lagged value have negative effect on manufacturing output.…”
Section: Resultssupporting
confidence: 79%
“…Several empirical studies are country-specific using time series data across several years while others are cross-country utilizing panel or cross sectional data. Chih-Hung Liu, et al (2008) investigated the causal relationship between GDP and public expenditures for US federal government covering the time series data 1974-2002, they found in this study that total expenditure does cause the growth of GDP, which is consistent with the Keynesian theory. However, the growth of GDP does not cause the increase in total public expenditure which is inconsistent with Wagner's law.…”
Section: Business and Economic Researchsupporting
confidence: 60%
“…However, in the most recent contribution to the subject by Narayan and Singh (2007) the authors report that their findings are consistent with the Keynesian school of thought. Liu et al (2008) present results on the association between public expenditure and economic growth using aggregate US data as well as disaggregate data with subcategories including national defence, human resource expenditure, physical resources expenditure, net interest payment and other expenditure. The results are mostly consistent with Keynesian theory.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Liu et al [31] examined the causal relationship between GDP and public expenditure for United States of America using data from the period 1947-2002. The causality results revealed that total government expenditure causes growth of GDP.…”
Section: Empirical Literaturementioning
confidence: 99%